Effect of Additives on Surface Tension, Viscosity, Transparency and Morphology Structure of Aloe vera Gel-Based Coating - Suriati, Luh; Utama, I. Made Supartha; Harsojuwono, Bambang Admadi; Gunam, Ida Bagus Wayan (Frontiers in Sustainable Food Systems, 2022)
Coating is a new trend for extending shelf-life and reducing postharvest damage to fruits currently. Aloe vera gel-based (AVG) coating is made by adding citric acid, ascorbic acid and potassium sorbate. The additive increases the stability of AVG coating. This research aims to determine the effect of additives on the surface tension, viscosity, transparency and morphology structure of AVG coating. The observation used a completely random design one factor with three replicates. Formulation of AVG coating uses additives involving citric acid, ascorbic acid, potassium sorbate and the mixture of additives, concentrations of 0.15%. Observations are made periodically on days 0, 5, 10 and 15. The type and concentration of additives affect the surface tension, viscosity, transparency and morphology structure of AVG coating. The best formulation of AVG coating for 15 days of storage is a mixture of additives (citric acid, ascorbic acid and potassium sorbate) with a concentration of 0.15% applied on the surface of the fruits. The best numeric value of AVG coating surface tension is 0.122 N/m, acidity 4.22, viscosity 96.03 mPa.s, color L* 19.51 and point of transparency 84.40. The combination of the three additives produced a clear, transparent white coating appearance and the potential to extend the shelf-life of fruit.